A Theological Study of the Impact of an Interreligious Marriage: Self-Adjustment in Couples from Different Religions - Rina Rifayanti; Ayunda Ramadhani; Nadya Novia Rahman; Nirita Zahra; Ken Affifa; Sakinah Adilah; Diana (Pharos Journal of Theology, 2024)
In the world in which we currently live, individuals of different religions may be involved in many dating relationships. Interfaith couples do not have a comfortable space in this set-up because of their different backgrounds and beliefs. Consequently, interfaith relationships come under much pressure from their environment, such as friendships and families. Problems often found in relationships between interfaith couples are obtaining approval from parents and family, the views of people around them, and conflicts resulting from interfaith relationships relating to issues of faith. Differences in religion and belief should factor in conflict between couples in interfaith relationships. Self-adjustment is very important to do and strive for to achieve happiness and find peace. This research undertaken was qualitative research using phenomenological methods. The data collection methods used were interviews and observation. The data collection technique used a purposive sampling technique. The data analysis technique consisted of preparing and processing data, reading all the data, coding, describing the coding results into themes being analyzed, presenting themes in narrative form, and interpreting the data. The research showed that the subjects were less able to adapt to the environment in interfaith marriages. The subject's emotional and social self-adjustment means that the subjects choose to undergo a relationship without thinking about the possibilities of what might happen in the future and ignore the opinions of the environment so that harmony and peace in the relationship are maintained. Future researchers can examine other factors regarding adjustment to interfaith relationships to discover new things experienced by students and others in interfaith relationships. Psychologically and sociologically, interfaith marriages can trigger and strengthen existing disputes. In addition, interfaith marriages are also considered to cause psychological and educational problems for children because they are confused about which religion to follow. Thus, allowing interfaith marriages often creates inconsistencies with the relevant legal provisions relating to guardianship, inheritance, and other related issues in such marriages.